MENGISYARATKAN SENTIMEN: SELAMAT DATANG, KPK JOKOWI! (SEBUAH PENDEKATAN APPRAISAL PADA TEKS BERITA) - Asrofin Nur Kholifah (PRASASTI: Journal of Linguistics, 2021)
This research examined the journalist sentiment in presenting news on the inauguration of KPK Supervisory Board. Through the Appraisal system, attitude, engagement and graduation were revealed to signify the journalist stance. A descriptive qualitative research was conducted by identifying social phenomenon which were then descriptively presented and analyzed. The data were taken from the online news portal of Tempo. The data were the news text entitled Selamat datang KPK Jokowi which highlighted the inauguration of KPK Supervisory Board. The result showed that the media represented by the journalist took a negative sentiment toward the issue proved by the dominance of negative judgment and appreciation along with the dominance of intensifiers and attitudinal lexis to support the motifs. Through those linguistic exploitation, the journalist led public perspective and opinion that the capacity, integrity and neutrality of Jokowi, DPR and KPK were questioned.